THE PREVALENCE AND CLINICAL CHARACTERISTICS OF PRIMARY HEADACHE IN IRRITABLE BOWEL SYNDROME: a subgroup of the functional somatic syndromes - SOARES,Rosa LS (2013)
ContextThe irritable bowel syndrome and primary headache are two chronic diseases characterized by symptoms of recurring pain and affect approximately 10%-20% of the general population.ObjectivesTo study the prevalence of primary headache in volunteers with irritable bowel syndrome in a Brazilian urban community.MethodsIt was evaluated the prevalence of primary headache associated with irritable bowel syndrome in adult volunteers 330 no patients.The protocol included the Rome III criteria, international classification of Headaches, later divided into four groups: I- Irritable bowel syndrome (n = 52), II- Primary headache (n = 45), III-Irritable bowel syndrome (n = 26) and headache, and IV- Controls (207).ResultsWe not found significant difference in the average age of the four groups and the diagnosis of irritable bowel syndrome, primary headache and their association was more frequent in females. The frequent use of analgesics was greater in groups II and III.ConclusionOur results suggest that irritable bowel syndrome and primary headache are also common in third world countries. The frequency in use of analgesics in association between the two entities was relevant. The identification of irritable bowel syndrome patients with different clinical sub-types could improve the therapeutics options and the prevention strategies.